(3HjGf GdCSQGQ hGdeYGfj GdehOYI aj GdMQR GdjeGfjs - (3GdMfaj, GdMQjQj, YKeGf Hf YHO Gddgs
(3ChdgG (B:s
(3GdMeO ddg GdPj ChbY aj CSQGQg eG TGA ajeG TGA ef GdcdeGJ hHYO ajbhd GdYHO GdabjQ GdebQ HGdYLQ hGdPfH GdcKjQ YKeGf Hf YHO Gddg GdMQjQj(B: (3gPg fHPI Ydi GdMQR GdjeGfjGdeSei HGdOYGA GdSjajhSejJgG HjGf GdCSQGQ hGdeYGfj GdehOYI aj GdMQR GdjeGfjs
(3BNQgG (B:s
(3bGd Udi Gddg Ydjg hSde eG ef YHO Xde aTNU HUQg Edi GdSeGA EdG bGd Gddg YR hLd(B: (3dHjc YHOj MbG dCfUQcs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs